Videoconferencing Psychotherapy During the Pandemic: Exceptional Times With Enduring Effects? - Fernández-Álvarez, Javier; Fernández-Álvarez, Héctor (Frontiers in Psychology, 2021)
With the advent of COVID-19, a sudden, unexpected and forced shift has been produced in the field of psychotherapy. Worldwide, many therapists closed their offices and started to deliver psychotherapy online through a screen. Although different media started to be incorporated, videoconferencing is undoubtedly the most common way in which therapists are doing therapy these days. This is catalysing a rapid change in the practice of psychotherapy with probable lasting effects and deserves to be carefully reflected upon. Therefore, in this paper our aim first to outline the main challenges for a medium that may have arrived to stay. In that sense, we review the literature to describe the state-of-the art regarding the main aspects of videoconferencing psychotherapy as well as to suggest possible avenues for future research and practice. Second, we aim to outline how the field of psychotherapy could benefit from this unprecedented situation.